PELATIHAN DAN PEMANFAATAN SEKAM PADI MENJADI BRIKET BIO ARANG SEBAGAI USAHA MIKRO MASYARAKAT DESA KEBON AYU - Zumrotin , Afifatuz; Maherani, Maherani; Jannah, Fadina Raodatul; Suryani , Mirna; Mujiddin , Khairul; Aryanti , Fhebby Novit; Ulfa , Khaira; Nufaidaf, Nufaidaf; Nurfadilah, Nurfadilah; Nalu , Syarifah Tinggi; Asrin, Asrin (Jurnal Wicara, 2023)
It is hoped that KKN students will be able to assist the West Lombok Trade and Industry Office in developing business and promotions, especially in Kebon Ayu Village, Gerung District, Lombok Regency. To prevent environmental pollution that occurs due to rice husks that are not managed properly, rice husks can be used as alternative fuels to replace kerosene, gas, wood charcoal and also organic fertilizers that are environmentally friendly. direct presentation of the material included: Explanation regarding rice husk briquettes and the reasons why rice husk briquettes have a selling price. How is the marketing explained here, marketing is done online through several Allshope accounts as well as direct marketing using brochures. How to make it that can be practiced directly by the community Community service activities in the form of rice husk briquette processing training were held on Tuesday, January 24 2023 in the kelebut hamlet field which was held at 16.00 - 18.00 WITA. training activities include delivering material explaining work programs, product background, product introductions, marketing plans. followed by a trial burning process, briquette processing training, question and answer session and group photos. Where in this case the Integrated Community Service Program students at the University of Mataram who focused on PKK mothers agreed because most of the mothers in this village only carried out activities at home as housewives.